PKM Dialogue Practice Read the dialogue aloud with your teacher. Alex is at the bank in the USA, opening a new account. Bank Clerk Good morning, sir. How can I help you? Alex Good morning. I’d like to open a savings account, please. Bank Clerk All right, s - Harahap, Olivia Feby (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
ABSTRACT Introduction: factors that cause students run into problems in learning English, among others lack of motivation, limited learning facilities, the absence of a container for them to practice vocabulary they have got, limited learning resources and shame to speak English. With the class room language makes it easy for students to remember the vocabulary which they have memorized. The aim of the study:To know About English and vocabulary used for classroom language in Junior High School Students at the Al Manar Orphanage, Ujung gurap. Materials and Methods: Extension activities about Using Classroom Language At Junior High School Students at the Al Manar Ujung Gurap Orphanage With the Lecture Method, Discussion and Question and Answer. Research result: Activities using Classroom Language get a positive response of students due to the class becomes even more active. Conclusion: As many as 87.5% of students have the ability in doing learning by using the classroom language.